2019
DOI: 10.1136/gutjnl-2019-319207
|View full text |Cite
|
Sign up to set email alerts
|

British Society of Gastroenterology position statement on patient experience of GI endoscopy

Abstract: This position statement provides a framework on patient experience of gastrointestinal endoscopy, with recommendations and suggestions for practice to ensure high quality patient experience. This area is not previously covered by British Society of Gastroenterology (BSG) guidelines or position statements and is an important addition to this field. The National Institute of Health and Care Excellence compliant BSG guideline development process was used throughout. A metanarrative review of the literature (syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…A preliminary literature review has shown heterogeneity in the types of instruments used to assess the patient experience and there is no existing consensus on how to prioritise measures of patient experience. 17 22 Therefore, studies reporting any quantitative measure of patient experience, including satisfaction, anxiety, pain or discomfort as an outcome, will be included. Secondary outcomes will include willingness to repeat the procedure, adenoma detection rate, polyp detection rate, caecal intubation rate, caecal intubation time, total colonoscopy time, endoscopist satisfaction, cost in dollars and the occurrence of any adverse events (eg, bleeding and perforation).…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary literature review has shown heterogeneity in the types of instruments used to assess the patient experience and there is no existing consensus on how to prioritise measures of patient experience. 17 22 Therefore, studies reporting any quantitative measure of patient experience, including satisfaction, anxiety, pain or discomfort as an outcome, will be included. Secondary outcomes will include willingness to repeat the procedure, adenoma detection rate, polyp detection rate, caecal intubation rate, caecal intubation time, total colonoscopy time, endoscopist satisfaction, cost in dollars and the occurrence of any adverse events (eg, bleeding and perforation).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The British Society of Gastroenterology’s position statement on patient experience during gastrointestinal (GI) endoscopy affirms not only patient experience as a core dimension of healthcare quality but also enumerates few options available to endoscopists to alter the patient experience during GI endoscopy. 17 To inform efforts to improve the patient experience of colonoscopy and potentially reduce the use of deep sedation for routine colonoscopy, additional research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The BSG position statement on patient experience of GI endoscopy states that discomfort, pain and embarrassment during the procedure should be controlled and kept to a minimum 23. The BSG colonoscopy guidelines recommend that rates of moderate-severe discomfort should be <10%.…”
Section: Recommendation Statementsmentioning
confidence: 99%
“…The BSG position statement on patient experience of GI endoscopy states that discomfort, pain and embarrassment during the procedure should be controlled and kept to a minimum. 23 The BSG colonoscopy guidelines recommend that rates of moderate-severe discomfort should be <10%. We recommend that this KPI should apply to FS and measured using the 5-point modified Gloucester comfort scale, 24 with nurse-reported scores of 4 and 5 indicating significant discomfort.…”
Section: Recommendation Statementsmentioning
confidence: 99%
“…Patient experience is a crucial marker of quality of GI procedures and impacts patient attendance and reattendance. All patient-reported experience measures should be patient centred; derived from and completed by patients 4. Previous GI endoscopy patient experience questionnaires were often developed by clinicians with little or no patient input, typically focused only on comfort and were recorded by healthcare professionals.…”
mentioning
confidence: 99%